2022
DOI: 10.1039/d2ta06557f
|View full text |Cite
|
Sign up to set email alerts
|

Oppositely charged MXene fibers as a highly efficient osmotic power generator from sea and river water

Abstract: Ion-exchange membrane-based reverse electrodialysis (RED) shows great potential for harvesting osmotic energy from seawater and converting it to electricity. However, their low energy conversion efficiency and huge ionic resistance hinder...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…The corresponding short‐circuit current ( I SC ) and open‐circuit voltage ( V OC , consisting of the diffusion potential [ V diff ] and the redox potential [ V redox ]; for calculation details see Supporting Information) could be recorded through directly measuring the intercepts on the current and voltage axes. [ 56 ] When the concentrated solution was applied to the SAMM‐2 side (c SAMM /c AAO = 1 m /1 m m ), the absolute values of V OC and I SC were 86.6 mV and 0.62 µA, respectively. The inner resistance ( R channel ) of the nanofluidic system could be calculated as R channel = V OC / I SC , which approximates to 140 kΩ.…”
Section: Resultsmentioning
confidence: 99%
“…The corresponding short‐circuit current ( I SC ) and open‐circuit voltage ( V OC , consisting of the diffusion potential [ V diff ] and the redox potential [ V redox ]; for calculation details see Supporting Information) could be recorded through directly measuring the intercepts on the current and voltage axes. [ 56 ] When the concentrated solution was applied to the SAMM‐2 side (c SAMM /c AAO = 1 m /1 m m ), the absolute values of V OC and I SC were 86.6 mV and 0.62 µA, respectively. The inner resistance ( R channel ) of the nanofluidic system could be calculated as R channel = V OC / I SC , which approximates to 140 kΩ.…”
Section: Resultsmentioning
confidence: 99%
“…The core component of RED is composed of selective osmotic membranes, and the fundamental issue with these osmotic membranes lies in their requirement to simultaneous possess high surface charge, high nanochannel density, and a certain degree of mechanical robustness. 19,20 Currently, numerous two-dimensional materials, including graphene, 21 graphene oxide, 22 molybdenum disulde, 23 MXene, 24 and boron nitride, 25 have been engineered for application as osmotic selective membranes in RED. The unique layered structure of two-dimensional materials can serve as nanouidic channels, and the specic regions modied with particular surface charges can form Debye double layers that facilitate ion transport, thus diminishing ion transport resistance while enhancing ion ux.…”
Section: Introductionmentioning
confidence: 99%
“…The application of two-dimensional materials in osmotic selective membranes for the generation of osmotic energy has revealed that electronic effects within nanouidic channels can achieve two-dimensional connement of ions and alter their transport. [21][22][23][24][25][26]28 Based on this, the constraints associated with two-dimensional materials can be effectively solved through the modication of interconnected nanochannels within hydrogel network structures possessing high surface charges. Upon conning ions within these nanochannels, the anions/cations exhibit dramatically distinct properties, driven by the surface charge on the inner channel wall, which induces repulsion of like-charged ions and attraction of counter-ions, causing them to be the primary charge carriers.…”
Section: Introductionmentioning
confidence: 99%